2020
DOI: 10.1038/s41396-020-00858-x
|View full text |Cite
|
Sign up to set email alerts
|

Selfishness driving reductive evolution shapes interdependent patterns in spatially structured microbial communities

Abstract: Microbes release a wide variety of metabolites to the environment that benefit the whole population, called public goods. Public goods sharing drives adaptive function loss, and allows the rise of metabolic cross-feeding. However, how public goods sharing governs the succession of communities over evolutionary time scales remains unclear. To resolve this issue, we constructed an individual-based model, where an autonomous population that possessed functions to produce three essential public goods, was allowed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 49 publications
3
36
0
Order By: Relevance
“…Nevertheless, our study also found that predictive function derived from the individual-based (IB) model with the assumption of mass well-mixing was not completely identical to the function from our ordinary differential equation (ODE) model, suggesting that other physical features of spatially structured environment may also contribute to the assembly of MDOL community. For example, the spatial distributions of different cell types in the colony are thought to represent another vital factor that governs community assembly [27, 5658]. In agreement with previous studies [31, 38, 59], our IB simulations suggested that when two populations engaged in MDOL, cells from the two populations are spatially more proximal to each other than the scenario when the two populations did not exhibit defined interactions (Supplementary Figure 27).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Nevertheless, our study also found that predictive function derived from the individual-based (IB) model with the assumption of mass well-mixing was not completely identical to the function from our ordinary differential equation (ODE) model, suggesting that other physical features of spatially structured environment may also contribute to the assembly of MDOL community. For example, the spatial distributions of different cell types in the colony are thought to represent another vital factor that governs community assembly [27, 5658]. In agreement with previous studies [31, 38, 59], our IB simulations suggested that when two populations engaged in MDOL, cells from the two populations are spatially more proximal to each other than the scenario when the two populations did not exhibit defined interactions (Supplementary Figure 27).…”
Section: Discussionsupporting
confidence: 89%
“…Here, in our study, we proved that this is also the case in the community engaged in MDOL. In addition, we reconfirmed that limited mass diffusion is one possible way to privatize public benefit [30, 37, 56]. On the one hand, it helps the Embezzler population to privatize the final product for its own growth.…”
Section: Discussionmentioning
confidence: 69%
“…To simulate the spatial competition between two populations, the BacGo model was built based on 2D lattices, following our previous framework(DK 1998; Kreft et al 1998;Wang et al 2020). In our model, a microhabitat was conceptualized as a 20×20 array.…”
Section: Basic Settings Of the Bacgo Modelmentioning
confidence: 99%
“…Abiotic spatially related factors may also be potential factors independent of biological intrinsic properties but affecting outcomes of the competition for space. Our previous study indicated that even if the initial abundance and inherent fitness of two populations were identical, outcomes of the spatial competition were not completely random but significantly influenced by the relative positions and time orders for the emergence of different genotypes (Wang et al 2020). These findings suggested that specific events that occurred during the space colonization affected which population colonized more space.…”
Section: Introductionmentioning
confidence: 99%
“…S9 and Table S8). According to the Black Queen Hypothesis, when an individual loses an energy-expensive function, it becomes a 'beneficiary', who scavenges the public goods, such as AAs, from other individuals (helpers) for survival [65,66]. The 'beneficiary' strain will expand in the community until the production of public goods, such as AAs, is just sufficient to support the balanced community.…”
Section: Biosynthetic Metabolism Of Acetate Oxidizersmentioning
confidence: 99%